TRAUMA AND HANGING- AN UNUSUAL CASE OF COMPLICATED SUICIDE (Indian Internet Journal of Forensic Medicine and Toxicology, 2024)
Suicidal deaths are very frequently encountered by forensic experts in day-to-day practice.  Here, we shed light on an unusual complicated suicide case, with features of hanging, head  trauma and traumatic asphyxia. Allegedly, a dead body of a 65 years old man was found stuck  in a shaft between the elevator and a wall, in a multistorey building, with ligature material placed  around his neck. The ligature material was torn in two parts and the other part was found tied  over the railing upstairs, in proximity to the elevator shaft, in front of his room. Suicide notes  were found with the body. During the autopsy, two loops of faint ligature marks were present on  the neck and on further exploration, extravasation of blood was present over the strap muscles  of neck and carotid sheath. Upper part of the body was congested and there was a clear line of  demarcation. Head injury was also present with skull fractures and cerebral haemorrhages.  Signs of asphyxia were seen on the internal organs. This case, illustrating a peculiar pattern of  injuries is reported for future reference of pathologists to help in identifying and anticipating such  injuries in similar cases of suicide.
Keywords: Suicide; Suicide Hanging; Head injury; Complicated suicide; Traumatic asphyxia